Data communications and networking - Forouzan, Behrouz A (New Delhi : Mcgraw Hill, 2013)
We are pleased to present this edition of Forouzan's Data Communications and Networking. It has been developed specifically to meet the need of students of computer networks. In addition to a chapter on the peer-to-peer paradigm, a full chapter on quality of service (QoS), generous coverage of forward error correction, coverage of WiMAX and material on socket-interface programming in Java, we have added new end-of-chapter questions and problems to make the content more relevant and improve learning outcomes for the student. Salient features:Follows Visual approach which gives the reader the opportunity to understand the networking concept with real-life application orientation.Coverage of encryption, security and synchronization in multi-processor systems is included with up-to-date information in the field. Demonstrate key issues concerning concepts and techniques through examples and case-studies.
Appendix A-H ; Glossary 1157-1192p.; References 1193-1198p.; Index 1199-1226p.
Keywords: Network models; Wireless lans; Multicast routing